EVALUATION OF OBSTRUCTIVE SLEEP APNEA SYNDROME AS A RISK FACTOR FOR DIABETIC MACULAR EDEMA IN PATIENTS WITH TYPE II DIABETES. Issue 2 (February 2019) - Vié, Anne-Laure; Kodjikian, Laurent; Agard, Emilie; Voirin, Nicolas; El Chehab, Hussam; Denis, Philippe; Coste, Olivier; Dot, Corinne
Abstract : Purpose: To evaluate the association between obstructive sleep apnea and diabetic macular edema (DME) in patients with Type II diabetes, using the apnea–hypopnea index and other nocturnal hypoxemia parameters. Methods: This cross-sectional, case–control study included 99 patients with Type II diabetes: the first group included patients with DME (DME+ group) and the second patients without DME (DME− group). Polysomnography was performed in all patients. The two groups were compared, and the risk factors were studied using logistic regression. Results: The DME+ group comprised 38 patients, and the DME− group comprised 61 patients, aged a mean 68.8 years and 66.3 years ( P = 0.27), respectively; mean body mass index was 29.7 and 30.9 ( P = 0.16), respectively. The mean apnea–hypopnea index was significantly higher in the DME+ group (43.95 [13.5–87.3]) than in the DME− group (35.18 [3.55–90.7]) ( P = 0.034). Patients with DME had more severe obstructive sleep apnea (apnea–hypopnea index >30) than the others: 71% versus 50.8% ( P = 0.049). Cumulative time of SPO2 below 90% (CT90%) was independently associated with DME after adjusting for confounding factors, whereas there was no difference between the oxygen desaturation index and minimum O2 saturation. Conclusion: Severe obstructive sleep apnea (apnea–hypopnea index >30) and parameters of nocturnal hypoxemia (cumulative time of SPO2 below 90%) are associated with DME. Abstract : Obstructive sleep apnea, responsible of nocturnal hypoxia, could increase the risk of diabetic macular edema on the diabetic population. This controlled study showed that there is a strong association between severe obstructive sleep apnea (AHI ≥30) and diabetic macular edema on Type II diabetic population. There is also a link between diabetic macular edema and desaturation parameters. Obstructive sleep apnea screening in patients with Type II diabetes seems justified.